AB0102 Pycnogenol ameliorate collagen-induced arthritis through modulating inflammatory mediators, decreases oxidative stress, and improves clinical signs in wistar rats. (23rd January 2014) - Umar, S.; Ahmad, S.; Katiyar, C.K.; Khan, H.A.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease which leads destruction of joints. Current treatment modalities for RA either produce symptomatic relief (NSAIDs) or modify the disease process (DMARDs) 1 . Though effective, their use is also limited by their side effects. As a result, the interest in alternative, well tolerated anti-inflammatory remedies has re-emerged 2 . Objectives: To assess antioxidant and antiarthritic potential of a pycnogenol in collagen induced arthritis in Wistar rats. Methods: Arthritis was induced in male Wistar rats by collagen induced arthritis (CIA) method. Pycnogenol 3.4 was administered at dose of 20 mg kg -1 body weight once daily for 21 days. The effects of treatment in the rats were assessed by biochemical (articular elastase, MPO, LPO, GSH, Catalase, SOD and NO), inflammatory mediators (IL-1β, IL-6, TNF-α, IL-10, IFN-γ, and PGE2 ) and histological studies in joints. Results: Pycnogenol was effective in bringing significant changes on all the parameters (articular elastase, MPO, LPO, GSH, Catalase, SOD and NO) studied in treated rats as compared to RA rats. Oral administration of pycnogenol significantly reduced the levels of inflammatory mediators (IL-1β, IL-6, TNF-α, IFN-γ, and PGE2 ) and increase level of IL-10. The protective effects of pycnogenol against RA were also evident from the decrease in arthritis scoring and bone histology. Conclusions: The fact that pycnogenol abolishes a number of factors known to be involved in RA. Therefore, this study indicates that the administration pycnogenol has significant potential in the treatments for chronic inflammatory diseases like rheumatoid arthritis as an alternative and safe therapy. References: Koelink PJ, Overbeek SA, Braber S, de Kruijf P, Folkerts G, Smit MJ, et al. Targeting chemokine receptors in chronic inflammatory diseases: An extensive review. Pharmacol Ther. 2012 Jan;133(1):1-18. Abdel-Tawab M, Werz O, Schubert-Zsilavecz M. Boswellia serrata: an overall assessment of in vitro, preclinical, pharmacokinetic and clinical data. Clin Pharmacokinet. 2011 Jun 1;50(6):349-69. Khan MM, Hoda MN, Ishrat T, Ahmad A, Khan MB, Khuwaja G, Raza SS, Safhi MM, Islam F. Amelioration of 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine-induced behavioural dysfunction and oxidative stress by Pycnogenol in mouse model of Parkinson's disease. Behav Pharmacol. 2010 Sep;21(5-6):563-71. Ince, O.Yesil-Celiktas, N.U.Karabay-Yavasoglu, G.Elgin Effects of Pinus brutia bark extract and Pycnogenols in a rat model of carrageenan induced inflammation. Phytomedicine 16 (2009) 1101–1104. Disclosure of Interest: None Declared